Contributions of the New Literacy Studies to the Field of Youth and Adult Education - Lorenzatti, Maria del Carmen; Blazich, Gladys; Arrieta, Rocío (Íkala, Revista de Lenguaje y Cultura, 2019)
This article deals with the contributions brought by the New Literacy Studies to the field of youth and adult education. This perspective and the ethno-graphic approach allow to record, analyse and conceptualize individuals’ everyday activities concerning written culture. Thus, the findings from two empirical research projects carried out in Argentina are presented here. In the first section, the methodological theoretical approach by nels is presented. Then, reading and writing practices are analyzed from the uses and mean-ings assigned to the school’s alphabet. In the following section it is possible to visualize how the relationships with the written culture in the school are configured from the reading of a story. Finally some reflections on the contri-bution of the nel to the Education of Young People and Adults in Argentina are presented.